Does a tragedy of the commons due to individual competition arise from genetically fixed traits or plastic traits in dryland wheat? An experimental verification. (8th February 2023) - Zhu, Li; Xiang, Jun; Zhang, Da-Yong; Wang, Wei; Zhu, Shuang-Guo; Wang, Bao-Zhong; Yang, Li-Yuan; Li, Meng-Ying; Xiong, You-Cai
Abstract: Growth redundancy, the overgrowth of resource-foraging organs in crop stands, is often detrimental to yield and is thus called a 'tragedy of the commons'. A tragedy can also arise owing to the plastic overproduction of competitive structures when intra-variety individuals forage in close proximity to each other. However, little is known about the sensitivity of crop varieties and resource availability to this 'plastic' tragedy. Pot experiments were designed to investigate this issue. The root competition environment was imposed by growing two plants of the same variety in mesh and plastic partitions. Two wheat varieties (old Monkhead and modern 92-46) were used, and two resource levels were established. Compared with 92-46, Monkhead allocated more biomass to stems and leaves and concurrently less to seeds. We identified intra-variety neighbour effects only in 4 out of 24 allometric comparisons with a small magnitude. Allometric data also revealed a lowered response to fertilizer addition in 92-46 than in Monkhead. Based on a limited sample size, our results revealed a trade-off between above-ground vegetative growth and crop yield. This trade-off resulted in a tragedy of the commons in old Monkhead and enhanced yields in modern 92-46. The tragedy of the commons in wheat may generally arise from genetically fixed traits in terms of growth redundancy in old varieties, rather than from the plastic behaviour of individuals. Modern 92-46 may adopt a conservative strategy of resource use, whereas old Monkhead employs an exploitative strategy. Our findings highlight breeders should select genotypes with low individual competitiveness.